2019
DOI: 10.7882/az.2018.031
|View full text |Cite
|
Sign up to set email alerts
|

What should we do with wild dogs? Taxonomic tangles and the management of dingo-dog hybridisation

Abstract: Taxonomy plays an important role in defining biodiversity and shaping conservation efforts. However, the biological species concept is a human construct and organisms that do not abide by the rules do not fit easily into conservation and policy frameworks. Organisms that are hybrids are one such example. Indeed, hybridisation can result in both the protection and persecution of wild organisms, especially if the hybrid status is uncertain. Here, we outline the issue of hybridisation between dingoes and dogs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Arguments to maintain dingo "purity" mean that dingo-dog hybridisation is used as justification for destruction [39] (similar to how wolf-dog hybrids are culled in Europe [40]). However, this denies some wild canids the right to exist based on mixed ancestry that resulted from human actions; for example, the introduction of domestic dogs to Australia [6]. We acknowledge that, like most wildlife, dingoes have significance for Australian Indigenous cultures [2] that is largely overlooked in dingo management.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Arguments to maintain dingo "purity" mean that dingo-dog hybridisation is used as justification for destruction [39] (similar to how wolf-dog hybrids are culled in Europe [40]). However, this denies some wild canids the right to exist based on mixed ancestry that resulted from human actions; for example, the introduction of domestic dogs to Australia [6]. We acknowledge that, like most wildlife, dingoes have significance for Australian Indigenous cultures [2] that is largely overlooked in dingo management.…”
Section: Discussionmentioning
confidence: 98%
“…There are varied examples of how people in different Indigenous communities sometimes distinguish types of dogs, for example, as dingoes and domestic dogs, or "camp dogs" and "wild dogs" (reviewed in [6,33]), yet little has been reported about how these distinctions are made. In the current study, strong agreement about the types of dogs in pictures from camera traps demonstrated the characteristics that residents in the Northern Peninsula Area (NPA) of Australia consistently classified as belonging to dingoes, including their acceptance of some characteristics associated with hybridisation with domestic dogs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, there is scientific debate about the dingo's trophic role in Australian ecosystems (Letnic et al ; Allen et al ). The dingo does not fit neatly into the categorizations we usually assign wild animals (Hytten ; van Eeden et al 2019b) because it was brought to Australia around 5,000 years ago, and thus viewed as either a native or introduced species by different stakeholders. Because hybridization between dingoes and domestic dogs has occurred, they are inconsistently labeled as “dingoes” or “wild dogs” by those who support their conservation and those who propose their control, respectively (Kreplins et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Concurrently, conflicting ideas on the management goals for WDH and other types of anthropogenic hybridization further reinforce the debate within the scientific community. On one hand, some researchers suggest managing admixed individuals on the bases of their ecological function (i.e., the concept of ecological surrogates; Daniels and Corbett, 2003;Glen, 2010;Fitzpatrick et al, 2015;Jackiw et al, 2015;van Eeden et al, 2018), increased evolutionary potential (Fitzpatrick et al, 2015;Jackiw et al, 2015;Wayne and Shaffer, 2016), or "cultural function" (Daniels and Corbett, 2003;Glen, 2010;van Eeden et al, 2018). On the other hand, all these ideas contradict the most influential guidelines on anthropogenic hybridization, which rather recommend preserving the genetic integrity of wild species (i.e., Allendorf et al, 2001).…”
Section: Introductionmentioning
confidence: 99%